Comparative genomic hybridization of oocytes and first polar bodies from young donors. - Fragouli, E; Escalona, A; Gutiérrez-Mateo, C; Tormasi, S; Alfarawati, S; Sepulveda, S; Noriega, L; Garcia, J; Wells, D; Munné, S (2009)
Chromosome abnormalities are common in oocytes derived from patients undergoing IVF treatment. The proportion of oocytes displaying aneuploidy is closely related to maternal age and may exceed 60% in patients over 40 years old. However, little information currently exists concerning the incidence of such anomalies in oocytes derived from young fertile women. A total of 121 metaphase II oocytes and their corresponding first polar bodies (PB) were analysed with the use of a comprehensive cytogenetic method, comparative genomic hybridization (CGH). The oocytes were donated from 13 young women (average age 22 years) without any known fertility problems. All oocytes were mature at the time of retrieval and were unexposed to spermatozoa. A low aneuploidy rate (3%) was detected. These results clearly indicate that meiosis I segregation errors are not frequent in oocytes of young fertile women. The higher aneuploidy rates reported in embryos derived from donor oocytes could be due to aggressive hormonal stimulation, in combination with male factors. However a definite contributing factor remains to be elucidated. The data obtained during this study also illustrate that CGH accurately and efficiently detects aneuploidy, confirming that it is suitable for application in a clinical setting for the assessment of oocytes, via PB analysis.